SOSIALISASI PENYUSUNAN LAPORAN KEUANGAN PADA IKM TS ALUMINIUM BERDASARKAN SAK EMKM DI KELURAHAN SOROSUTAN - Rizky Dwinanti; Moch. Imron (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Based on the pre-survey that has been carried out in the field, it is known that IKM TS Aluminum has not used financial reports that are by the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) because they are still experiencing problems in managing and compiling financial reports. The financial information management at IKM TS Aluminum still uses the manual method, and the reporting is still internal (according to the owner's interests). With financial management that is still manual and the reporting needs to be by economic standards, this is the problem in this service. From the results of the survey, servants are encouraged to conduct socialization and training on understanding and knowledge of how to make financial reports based on financial standards, as well as the hope that partners as EMKM understand and know about the proper and correct implementation of creating financial reports according to SAK EMKM. Based on the pre-test results, most partners still need to understand the preparation of financial statements by SAK EMKM in the form of financial position, income statements, cash flow statements, and reports of changes in capital. After the socialization and training of partners, the post-test results showed that the partners understood and understood the preparation of financial statements by SAK EMKM in the form of financial position, cash flow statements, income statements, and reports of changes in capital.